2013
DOI: 10.1002/j.0022-0337.2013.77.9.tb05586.x
|View full text |Cite
|
Sign up to set email alerts
|

Self–Directed Study and Carving Tooth Models for Learning Tooth Morphology: Perceptions of Students at the University of Aberdeen, Scotland

Abstract: Tooth morphology has been taught at the University of Aberdeen Dental School, United Kingdom, through self-directed workshops, using online handouts and tooth models. Tooth carving sessions were recently added to introduce manual skills training through learning tooth morphology at an early stage of the dental course. The aim of this study was to assess students' perception of both teaching modalities to evaluate their usefulness and to allow further course development. The subjects of this study were irst-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 17 publications
0
37
0
3
Order By: Relevance
“…In addition to scientific knowledge, the student must possess an ability to develop the manual skills necessary for the practical application of this knowledge (McHarg and Kay, ; Eid et al, ). There is a wide variety of teaching techniques that any teacher can adapt to his/her teaching style, the characteristics of the students, and the classroom (Eid et al, ; de Azevedo Rde et al, ; Magne, ; Bakr et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to scientific knowledge, the student must possess an ability to develop the manual skills necessary for the practical application of this knowledge (McHarg and Kay, ; Eid et al, ). There is a wide variety of teaching techniques that any teacher can adapt to his/her teaching style, the characteristics of the students, and the classroom (Eid et al, ; de Azevedo Rde et al, ; Magne, ; Bakr et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the age‐old exercise of carving using wax remains the gold standard when compared to E‐learning techniques (Patil et al, ). Wax carving continues to be the most used method for teaching tooth morphology in schools worldwide (Eid et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…4,5,9,10 However, few suggested it helped to develop psychomotor skills and manual dexterity. 3,11 In addition, the knowledge helped in restorative and prosthodontic procedures. 3 Many studies have suggested to use new methods along with the traditional methods of teaching.…”
Section: Discussionmentioning
confidence: 99%
“…15 Teaching tooth morphology has also been supplemented with digital atlases. 11 These days newer methods have been utilized as an alternative way to enhance and support the traditional methods such as digital methods utilizing computer graphics methods and online teaching methods have also been adopted in many countries. 16,17 The use of computer assisted instruction along with traditional wax carving have also been suggested to enhance the learning capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the cost, number of students, and staff's difficulty, lessons of carving tooth models in wax or soap had been dropped in some university [5]. Alternatively, self-directed workshops using online handouts and digital tooth model to teach carving and tooth morphology was proposed to meet teaching requirements.…”
Section: Introductionmentioning
confidence: 99%